2015
DOI: 10.1136/bjophthalmol-2014-306343
|View full text |Cite
|
Sign up to set email alerts
|

Changes in choroidal thickness during pregnancy detected by enhanced depth imaging optical coherence tomography

Abstract: Choroidal thickness was found to be significantly decreased in healthy pregnant women during the third trimester compared to the first trimester. This finding can provide valuable information when interpreting pregnancy related ocular disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…Vance et al 40 showed the effects of sildenafil citrate (phosphodiesterase-5 inhibitor) on the choroidal thickness by vasodilatory effect of nitric oxide. Dadaci et al 41 compared the choroidal thickness measurements of healthy pregnant women obtained in the first trimester with measurements obtained in the third trimester. They reported a significant decrease in choroidal thickness in the period of the third trimester due to vasoconstriction related to the increased adrenoreceptor activity and higher α1-adrenoreceptor concentration in this period.…”
Section: Discussionmentioning
confidence: 99%
“…Vance et al 40 showed the effects of sildenafil citrate (phosphodiesterase-5 inhibitor) on the choroidal thickness by vasodilatory effect of nitric oxide. Dadaci et al 41 compared the choroidal thickness measurements of healthy pregnant women obtained in the first trimester with measurements obtained in the third trimester. They reported a significant decrease in choroidal thickness in the period of the third trimester due to vasoconstriction related to the increased adrenoreceptor activity and higher α1-adrenoreceptor concentration in this period.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies [2, 21-31] with a total of 1,053 participants (479 healthy pregnant women and 574 healthy nonpregnant women) were included. As shown in Figure 2, the CT of the healthy pregnancy group (μm, WMD = 34.19, 95% CI: 20.63–47.76) was significantly higher than the controls (Test of WMD = 0: z = 4.94, p = 0.000).…”
Section: Resultsmentioning
confidence: 99%
“…At different pregnant periods, changes in the CT have been found. Goktas et al [26] suggested that choroid could be thickened during the second trimester, and Dadaci et al [2] found that the CT was significantly decreased in healthy pregnant women during the third trimester compared to the first trimester. Second, except for those discussed above, there still exist variables that might differ among studies, such as the diopters of the eyes and the intraocular pressures.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, 10 studies have been done to discover the association between choroidal thickness and pregnancy [37, 5260]. And the age of volunteers in all groups was matched.…”
Section: The Choroidal Thickness In Gestationmentioning
confidence: 99%